2013
DOI: 10.1111/sjop.12042
|View full text |Cite
|
Sign up to set email alerts
|

ADHD symptoms, academic achievement, self‐perception of academic competence and future orientation: A longitudinal study

Abstract: In the investigation of the effect of attention deficit hyperactivity disorder (ADHD) symptoms on school careers there is a need to study the role of adolescent and childhood ADHD symptoms and academic achievement, and to incorporate measures that include the individual's perspective. Our aim was to gain an overview of the long-term development of school careers in relation to ADHD symptoms. We studied associations between ADHD symptoms and academic achievement at different time-points and future orientation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 34 publications
8
50
1
2
Order By: Relevance
“…This is consistent with a previous survey conducted with a community sample (18). The authors found that severe inattentive symptoms were associated with decreased self-perception in terms of scholastic and athletic competence, both of which are related to school activities and classes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with a previous survey conducted with a community sample (18). The authors found that severe inattentive symptoms were associated with decreased self-perception in terms of scholastic and athletic competence, both of which are related to school activities and classes.…”
Section: Discussionsupporting
confidence: 93%
“…One study found a significant relationship between parent-rated and self-reported ADHD symptoms in adolescents aged 13 (17). Scholtens et al (18) conducted a community sample study and reported that ADHD symptoms had a negative effect on academic progress and academic self-perception. Additionally, Glass et al (19) examined the relationship between self-esteem and conduct problems in adolescents with ADHD and reported that self-esteem was significantly lower in adolescents with ADHD and conduct problems but not in adolescents with ADHD only.…”
Section: Introductionmentioning
confidence: 99%
“…About 80–85% of pre-teens continue to experience symptoms into the adolescent years and 60% into adulthood 810 . Adolescents with ADHD have difficulties in sustaining attention in routine tasks 1 , academic performance 11 , peer relations (e.g., increased victimization), and family cohesiveness 1215 . Untreated patients have higher rates of risky sexual behaviors 12 , suicidal thoughts in college 16 , incarcerations 13 , automobile accidents 17,18 , occupational difficulties and medical burden 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with ADHD have difficulties in sustaining attention in routine tasks 1 , academic performance 11 , peer relations (e.g., increased victimization), and family cohesiveness 1215 . Untreated patients have higher rates of risky sexual behaviors 12 , suicidal thoughts in college 16 , incarcerations 13 , automobile accidents 17,18 , occupational difficulties and medical burden 19 . They have lower self-esteem, social functioning, economic achievement and higher rates of substance use 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Although children falling under the globally steadily increasing diagnosis of ADHD have been shown to have academic and social difficulties (e.g., Ohlmeier 2008;Scholtens, Rydell & Yang-Wallentin, 2013), these possible adverse trajectories cannot be explained solely in terms of inadequate cognitive processes.…”
Section: Introductionmentioning
confidence: 99%